Exploring the Informal Learning Resources Used by Dental Students: A Mixed Method - Maha Akkari; Mayssoon Dashash; Issam Jamous (Journal of Medical Education and Curricular Development)
Background Informal learning resources can be considered supportive to formal learning resources in shaping future professional identity. This study aimed to assess dental students’ preferences towards using informal learning resources, to explore challenges impacting students’ choices and to find out the motivations for using these resources. Methods A mixed methods study design was conducted. A total of 1000 dental students completed a quantitative questionnaire data from different universities in Syria, and qualitative semi-structured interviews (15: postgraduate student and 30: undergraduate students) were fulfilled. Data were separately collected and analyzed. Results Peer learning scored a high level of engagement (undergraduates: 76.2%, postgraduates: 79.6%) as did the use of social media platforms (undergraduates: 79.4%, postgraduates: 80.6%). The challenges associated with utilizing open educational resources (undergraduates: 71.6%, postgraduates: 73.2%), social media platforms (undergraduates: 73.8%, postgraduates: 74.4%), and attending conferences and workshops (undergraduates: 75.4%, postgraduates: 76.2%) were rated at a high level. The undergraduate interview participants reported that lack of time was the most important limitation for using informal learning resources whereas online payment problem for open educational resources was basic challenge for postgraduate participants. Conclusions Reliance on informal learning resources is an efficient and vital tool for dental students. Faculty members can play an impact role in guiding students how effectively use of informal learning resources to enhance their educational experience.